A model for spatial spreading and dynamics of fox rabies on a growing domain - Yue Meng; Zhigui Lin; Michael Pedersen (Electronic Journal of Qualitative Theory of Differential Equations, 2020)
In order to explore the impact of the growth rate of the habitat on the transmission of rabies, we consider a SEI model for fox rabies on a growing spatial domain. The basic reproduction number is introduced using the next infection operator, spectral analysis and the corresponding eigenvalue problem. The stability of equilibria is also established using the upper and lower solutions method in terms of this number. Our results show that a large growth rate of the domain has a negative impact on the prevention and control of rabies. Numerical simulations are presented to verify our theoretical results.